Pengaruh Faktor Makroekonomi Terhadap Nilai Aktiva Bersih Reksa Dana Periode 2017-2021 - Kayla Suci Dinanty; Immas Nurhayati; Renea Shinta Aminda (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
The purpose of this study is to ascertain how Exchange Rates and Inflation Net Asset Value of Mutual Funds in Indonesia for the 2017-2021 Period. The sample used is some mutual fund products totaling 12 products from the number of Mutual Fund Investment Managers registered with the Financial Services Authority. This study used quantitative data and secondary data. Classic assumption test, multiple linear regression analysis, coefficient of determination (R2) and hypothesis tes tis the method used in this study with Exchange Rate (X1) and Inflation (X2) as independent variables and Net Aset Value (Y) as dependent variables. The findings revealed that the exchange rate had a little impact with a coefficient value of -0.03 and a probability value 0.72 > 0.05 and the NAV of Mutual Funds was significantly negatively impacted by inflation with a coefficient value of -132.54 and a probability value 0.01 < 0.05. The probability value is simultaneously computed as 0.00 < 0.05, indicating that the Exchange Rate and Inflation significantly affect Net Aset Value.